Head injury and limb fracture in modern playgrounds. Issue 2 (21st January 2004) - Norton, C; Rolfe, K; Morris, S; Evans, R; James, R; Jones, M D; Cory, C; Dunstan, F; Sibert, J R
Abstract : There were no serious head injuries in modern Cardiff municipal playgrounds with safety surfaces over five years injury surveillance. The literature suggests serious head injuries did occur before the introduction of safety surfaces.